2012
DOI: 10.1111/j.1365-2486.2012.02736.x
|View full text |Cite
|
Sign up to set email alerts
|

Future climate change driven sea‐level rise: secondary consequences from human displacement for island biodiversity

Abstract: Sea-level rise (SLR) due to global warming will result in the loss of many coastal areas. The direct or primary effects due to inundation and erosion from SLR are currently being assessed; however, the indirect or secondary ecological effects, such as changes caused by the displacement of human populations, have not been previously evaluated. We examined the potential ecological consequences of future SLR on >1,200 islands in the Southeast Asian and the Pacific region. Using three SLR scenarios (1, 3, and 6 m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
67
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 63 publications
0
67
0
1
Order By: Relevance
“…The interactions between crop suitability and conservation are not one-way interactions, as consumer preference for environmentally friendly production may penalize commodities that have novel or disproportional impacts on nature. The literature on indirect impacts of climate change on conservation is growing, including, for instance, the potential conservation impacts of human populations displaced by sea level rise (41). Indirect impacts of change in agriculture on ecosystems and their services has an important place in this growing body of research (15) Adaptation strategies are available to wine growers to maintain productivity and quality as well as to minimize freshwater withdrawals and terrestrial footprint (39).…”
Section: Discussionmentioning
confidence: 99%
“…The interactions between crop suitability and conservation are not one-way interactions, as consumer preference for environmentally friendly production may penalize commodities that have novel or disproportional impacts on nature. The literature on indirect impacts of climate change on conservation is growing, including, for instance, the potential conservation impacts of human populations displaced by sea level rise (41). Indirect impacts of change in agriculture on ecosystems and their services has an important place in this growing body of research (15) Adaptation strategies are available to wine growers to maintain productivity and quality as well as to minimize freshwater withdrawals and terrestrial footprint (39).…”
Section: Discussionmentioning
confidence: 99%
“…Virah-Sawmy et al 2009;Kirwan et al 2010;Holland 2012;Mendoza-González et al 2013;Hunter et al 2015), with few recent exceptions (e.g. Wetzel et al 2012;Faridah-Hanum et al 2014;Latinne et al 2015) the effect of climate change on coastal tropical terrestrial habitats is still an underrepresented field, and a body of research to which this study contributes. In closing, then we suggest that there are notable implications for conservation arising from the Hang Trống study.…”
Section: Resultsmentioning
confidence: 99%
“…Despite considerable attention to global change effects, few studies focused on the consequences of sea level rise (Menon et al 2010;Wetzel et al 2012;Schmidt et al 2012). Many studies showed that global warming will be one of the biggest threat to future biodiversity, and predictions could play an important role in alerting scientists and decision makers to support the development of proactive strategies to reduce climate change impacts on biodiversity (Bellard et al 2012).…”
Section: Introductionmentioning
confidence: 99%